Impact of Production Sharing Contract Price Sliding Royalty: The case of Nigeria’s Deepwater Operation - Okoro, Emmanuel E.; Okoye, Lawrence U.; Okafor, Ikechukwu S.; Obomanu, Tamunotonjo; Adeleye, Ngozi (International Journal of Energy Economics and Policy, 2021)
Petroleum fiscal regime has been a controversial issue in Nigerian economy. The basic issue is which regime will lead to the greatest benefit to the government without negatively affecting the performance of the international oil companies. Nigeria has in the past used different regime and had adopted the current price sliding royalty regime in 1996. The aim of this study is to examine how the new price sliding royalty affects the stake of government and contractors. This study adopts ex-post research design approach using data from various sources between 1980 and 2019. The autoregressive distributed lag (ARDL) regression approach was adopted for the data analysis. The unit root results reveal that the time series data consists of a mix of I(1) and I(0) variables. The ARDL Bound cointegration test shows that all the variables specified in the models have long run relationship. Estimates from the models indicate that the royalty regime in the Deep Offshore and Inland Basin Production Sharing Contract has positive and significant impact on the stake of government in the long and short runs, but negative impact on the stake of contractors. Furthermore, the royalty regime has negative impact on contractors’ performance in the long run. However, the impact on the three fiscal indicators (oil revenue, government expenditure, and deficit-GDP ratio) is positive. The study therefore recommends the repeal of the Nigerian petroleum fiscal policy with the new price sliding royalty to encourage investment and development of the petroleum sector. Keywords: Deepwater; Fiscal sustainability; Government and Contractor takes; Price sliding; Royalty regimes JEL Classifications: P28, O22, O38 DOI: https://doi.org/10.32479/ijeep.10837